(untitled) (The Journal of Sindhuli Multiple Campus, 2026)
The purpose of this study is to look into the function and effects of remittances on the Nepalese economy. For many developing nations, like Nepal, remittances have grown to be a sizable source of income. The different aspects of remittances, including their economic, social, and demographic ramifications, will be examined in this paper. It will include a thorough examination of how remittances affect important economic metrics like GDP growth, employment, the reduction of poverty, and consumption trends in Nepal. This research explores the potentialities and difficulties related to remittance flows and too offer policy suggestions to maximize the favorable effects and reduce the unfavorable outcomes. This in-depth research is focused on general history and overall phases of remittance provides the instances for sound economic move. Remittance plays a vital role in Nepal’s economic development, contributing significantly to GDP, poverty reduction, and household income. It supports consumption, education, and investment, while also stabilizing the national economy despite challenges like dependency and labor migration. This study investigates these key research questions: Nepal’s reliance on remittances, focusing on structural obstacles that limit their productive use and economic diversification, the effects of male out-migration on gender roles, household decision-making, and rural agriculture, and the vulnerability and resilience of households and the national economy to external political and economic shocks. The main objective of this research study is to analyze the impact of remittance on Nepal’s economic development and identify ways to promote its productive use for sustainable growth, to encourage the related stakeholders to seek the promotional measures for less dependency, also to assess the long term impact of remit based economy. A mixed-method research design is adopted, using both quantitative data (secondary sources such as national economic reports) and qualitative insights. Statistical analysis is employed to identify trends and relationships between remittance inflow and economic indicators. The findings reveal that remittance significantly boosts household income, reduces poverty, and supports foreign exchange reserves. However, it is largely spent on consumption rather than productive investment, limiting its potential for long-term economic transformation. Nepal’s heavy dependence on remittance raises concerns about long-term economic sustainability, limited domestic job creation, and productive investment. The research problem explores how remittance can be effectively utilized to promote sustainable economic growth and reduce structural dependency. In conclusion, while remittance plays a crucial role in economic stability, policies are needed to channel it into productive sectors to ensure sustainable economic development.